Gene expression networks in COPD: microRNA and mRNA regulation - Ezzie, Michael E; Crawford, Melissa; Cho, Ji-Hoon; Orellana, Robert; Zhang, Shile; Gelinas, Richard; Batte, Kara; Yu, Lianbo; Nuovo, Gerard; Galas, David; Diaz, Philip; Wang, Kai; et al. (Thorax, 2012)
BackgroundThe mechanisms underlying chronic obstructive pulmonary disease (COPD) remain unclear. MicroRNAs (miRNAs or miRs) are small non-coding RNA molecules that modulate the levels of specific genes and proteins. Identifying expression patterns of miRNAs in COPD may enhance our understanding of the mechanisms of disease. A study was undertaken to determine if miRNAs are differentially expressed in the lungs of smokers with and without COPD. miRNA and mRNA expression were compared to enrich for biological networks relevant to the pathogenesis of COPD.MethodsLung tissue from smokers with no evidence of obstructive lung disease (n=9) and smokers with COPD (n=26) was examined for miRNA and mRNA expression followed by validation. We then examined both miRNA and mRNA expression to enrich for relevant biological pathways.Results70 miRNAs and 2667 mRNAs were differentially expressed between lung tissue from subjects with COPD and smokers without COPD. miRNA and mRNA expression profiles enriched for biological pathways that may be relevant to the pathogenesis of COPD including the transforming growth factor β, Wnt and focal adhesion pathways. miR-223 and miR-1274a were the most affected miRNAs in subjects with COPD compared with smokers without obstruction. miR-15b was increased in COPD samples compared with smokers without obstruction and localised to both areas of emphysema and fibrosis. miR-15b was differentially expressed within GOLD classes of COPD. Expression of SMAD7, which was validated as a target for miR-15b, was decreased in bronchial epithelial cells in COPD.ConclusionsmiRNA and mRNA are differentially expressed in individuals with COPD compared with smokers without obstruction. Investigating these relationships may further our understanding of the mechanisms of disease.